æ±‰è¯åŠ¨è¯é‡å å½¢å¼åè¯¯åˆ†æž ï¼ˆä»¥ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸šå¤§äºŒå¦ç”Ÿä¸ºä¾‹ï¼‰ - Martini, .; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
æ‘˜è¦: é‡å æ˜¯æ±‰è¯çš„ä¸€ç§é‡è¦çš„è¯æ³•æ‰‹æ®µï¼Œå…¶ä¸åŠ¨è¯é‡å å½¢å¼å¤æ‚ã€ åŠŸèƒ½å¤šæ ·ã€è¯ä¹‰ä¸°å¯Œã€‚åŠ¨è¯é‡å ä½œä¸ºä½¿ç”¨è¾ƒå¤šçš„è¿™ç§é‡å ä¸€ç›´æ˜¯è¯è¨€ç•Œç ”ç©¶çš„é‡ç‚¹ï¼Œä¹Ÿæ˜¯å¤–å›½äººå¦ä¹ æ±‰è¯çš„ä¸€å¤§éš¾ç‚¹ã€‚ä¸ºäº†äº†è§£ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒ å¦é™¢æ±‰è¯ä¸“ä¸šå¤§äºŒå¦ç”ŸæŽŒæ¡æ±‰è¯åŠ¨è¯é‡å å½¢å¼çš„æƒ…å†µã€å‡ºçŽ°çš„é—®é¢˜åŠäº§ç”Ÿ åè¯¯çš„åŽŸå› ï¼Œç¬”è€…ä½¿ç”¨æè¿°æ€§ç ”ç©¶æ³•ä¸Žæ–‡çŒ®ç ”ç©¶æ³•å¯¹å¤§äºŒ39ä½å¦ç”Ÿä½¿ç”¨Â  åŠ¨è¯é‡å å½¢å¼äº§ç”Ÿçš„åè¯¯è¿›è¡Œç»Ÿè®¡ä¸Žåˆ†æžï¼Œå‘çŽ°äº†é—®é¢˜æ‰€åœ¨ï¼Œå¹¶æå‡ºç›¸å…³ å»ºè®®ã€‚é€šè¿‡ç ”ç©¶ï¼Œç¬”è€…å‘çŽ°å¦ç”Ÿå¾ˆå°‘ä½¿ç”¨æ±‰è¯åŠ¨è¯é‡å å½¢å¼è¿›è¡Œæ—¥å¸¸äº¤é™…ã€å¾ˆå°‘ä½¿ç”¨è¯å…¸ã€å¯¹æ±‰è¯åŠ¨è¯é‡å å½¢å¼ä¸ç†Ÿæ‚‰ã€ä¸çŸ¥é“åŠ¨è¯é‡å å½¢å¼çš„ç”¨æ³• ä¹Ÿå°†å½±å“æ±‰è¯åŠ¨è¯é‡å å½¢å¼çš„å›°éš¾ã€‚ å…³é”®è¯ï¼šæ±‰è¯åŠ¨è¯é‡å å½¢å¼ åè¯¯åˆ†æž Abstract: Reduplication is one of the important part of Mandarin grammar because the verb forms are complicated. Itâ€™s has many functions and contains many kinds of meaning. Reduplication verb is often used as the emphasis in language research. In addition, reduplication verb is a difficult point for foreign learners in learning Mandarin. The writer used descriptive study and literature research method to understand the learners learning condition, to conclude the problem that arise and the causes of the problems in learning reduplication verb forms in Mandarin towards 39 the fourth semester students of Mandarin language study program of Tanjungpura University. In this research, the writer found many students seldom used the reduplication verb forms to have some conversations, seldom used a dictionary, they are not understand the reduplication verb forms with their functions, and also influence others problem in using the reduplication verb forms. Keywords:Â  Reduplication Verb Forms in Mandarin, Error Analysis